Structure of hypothalamic nuclei, the nucleus preopticus (NPO) and its seasonal changes in relation to ovarian cycle of a freshwater carp, Labeo rohita (Ham.) - Sinhababu, D P; Sarkar, S K; Choudhuri, D K (Indian Journal of Fisheries, 2011)
Structure and circa-annual changes in the morphohistology (cell size andnumber) and cytology of hypothalamic nuclei - the nucleus preopticus (NPO)were studied in relation to ovarian cycle of a fresh water carp, Labeo rohita(Ham.). The NPO are paired, broad and oblong in shape, situated on eitherside of the third ventricle, anterodorsal to the optic chiasma. The NPO isdifferentiated as dorsal, scattered larger neurones, the pars magnocellularis(PMC) and ventral, smaller neurones - the pars parvocellularis (PPC). TheNPO neurones significantly increase in size and number and accumulate moreneurosecretory material (nsm) from early prespawning phase (February) of thegonad, reaching peak during maturing period (March - April). Thereafter, theneurones decrease in size along with the reduction of nsm, followed by decreasein number during spawning phase (June-August). The NPO cells remaininactive during postspawning phase (September-October) to early restingphase (November), but gradually get activated thereafter.